ANALISIS YURIDIS TERHADAP PERMOHONAN IZIN (DISPENSASI) NIKAH BAGI ANAK DIBAWAH UMUR - Suhaila Zulkifli (Universitas Islam Sumatera Utara, 2019)
AbstractMarriage is a bond between a man and a woman if both have reached the age limit set based on the applicable law. Marriage dispensation is a request for ratification of the marriage in which the brides or one of them has not reached the minimum age as stipulated in Law Number 1 of 1974 concerning Marriage. Thus, the determination of the Religious Court regarding marital dispensation is very important to carry out the process of legal rules for the continuity of the underage marriage. In this study, the writer uses library research. The meaning of this research is to interpret or say which is basically a way to solve existing problems; then, the data is collected, compiled, and concluded. The purpose of this study is to find out the judge's consideration in granting a marriage permit request for the underages, to find out the legal basis for judges in granting requests for marriage permits for them as well as to know the legal consequences after the underage marriage in the establishment of marriage permit in Pengadilan Agama Medan.